An atomistic Green's function method hybrid with a substructure technique for coherent phonon analysis. (1st September 2016) - Gu, Yunfeng; Wu, Xiaoli; Ni, Xiaoyu
ABSTRACT: By virtue of substructure technique, the atomistic Green's function method can be applied to efficiently evaluate the coherent phonon transport in a large device. Comprised of several substructures without inner atoms, the device can be described by a small system of algebraic equations, which can give a small but crucial submatrix of the retarded Green's function of the open device without loss in accuracy. While avoiding solving the entire device problem, the method can basically give all the information to describe the quantum transport within the ballistic limit, such as the transmission function and local density of states. The validity and efficiency of the proposed method is demonstrated by the one- and three-dimensional cases. The multilevel substructure technique is also feasible.